Pengembangan Gim Edukasi 2D Aturan Lalu Lintas Kendaraan Bermotor Berbasis Android - Faris Rafa Argadiraksa; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
in an effort to spread lectures about traffic regulation, this research aims to create an educational game that has content of ruiles and traffic signs as an another learning alternatives in the hope of reducing the number of commuters who do not understand traffic ruiles and signs, where this statement is backed up by data that describe the high number of traffic violations in Indonesia. The research method uses GFLC where the game enters six stages of development, namely the intiation, pre-production, production, testing, beta, and release stages. The results of the research provide a very good feedback for the game, such as increasing the knowledge of its users even though the user claims to have understood the traffic rules. These results provide the evidence that this educational game can be a good learning alternative.